From Boxing to Philosophy - Kosiewicz Jerzy (Physical Culture and Sport: Studies and Research, 2016)
This article begins the cycle of portraits of the members of the Editorial Board and Editorial Advisory Board of the journal Physical Culture and Sport. Studies and Research, who are eminent social scientists researching the issue of sport. Among them, there are many world-class professors, rectors and deans of excellent universities, founders, presidents and secretaries-general of continental and international scientific societies and editors of high-scoring journals related to social sciences focusing on sport. The journal Physical Culture and Sport. Studies and Research started its activities in 2008 and gathered many readers, distinguished authors and outstanding reviewers. It is worth taking a moment to present the profiles of the individual editors, thanks to whom the journal keeps getting better and better. The journal is increasingly appreciated internationally particular among the scientists from the humanist and social areas of investigations. The rapidly increasing number of its readers and its surprisingly wide reception, indicated by the number of visits and downloads in English-speaking countries, including hundreds of universities (up to 791 were interested in the content of issue 62 of our magazine), research institutes and related libraries, as well as academics, researchers and students, should be celebrated. These data are derived only from one bibliographic data base (EBSCO). It must be noted that the journal is indexed in 43 bases.